Percepatan Vaksinasi Covid-19 Bagi Kelompok Lansia: Percepatan Vaksinasi Covid-19 Bagi Kelompok Lansia - Sri Dinengsih; Eka Oktavia (J.Abdimas: Community Health, 2023)
The first case of COVID-19 in Indonesia was confirmed by the government in early March 2020. This virus is growing rapidly throughout the world, especially in big cities such as the Special Capital Region of Jakarta. The elderly group has risk factors up to 60 times more severe than children -children, more than 95% of deaths due to Covid-19 occurred in the elderly. More than 50% of all deaths occurred in elderly people over the age of 80. During the pandemic, it was recorded that the group requiring hospital treatment was dominated by the elderly. As a group that is very vulnerable to being exposed to COVID-19, the government is prioritizing the elderly to receive the COVID-19 vaccine. The aim of community service activities This is to accelerate the vaccination target for the elderly group in the working area of ​​the Pulogadung sub-district health center, East Jakarta. The subject of this activity is a group of people aged 60 years and over. At SMKN 26 in the working area of ​​the Pulogadung sub-district health center, vaccination was carried out. The vaccination implementation method goes through 3 stages: Direction, Implementation and evaluation. Conclusion: vaccination achievement target reached 87%. as many as 77 people, or 13%, did not meet the requirements to carry out the Covid-19 vaccination because the elderly participants had comorbid diseases such as high blood pressure. Advice is expected for elderly people who will carry out vaccinations to maintain their previous health and for elderly people who have get the vaccine so that you come back for the second vaccine schedule.